Cervical intraepithelial lesions among HIV infected patients - Silva, Ricardo J.O.; Reis, Aldo F.F.; Russomano, Fábio B.; Fialho, Susana C.A.V.; Grinsztejn, Beatriz (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]